(untitled) (Revista Electrónica Calidad en la Educación Superior, 2018)
The purpose of this article was to describe the methodology used for the analysis of similarity between grade careers that involved one or more Academic Units. This methodological study contemplated aspects of the creation of conglomerate accreditation commission, the elaboration of a work plan, the analysis and results of the careers’ affinities and possible challenges that are faced in these processes. It is concluded, that careers with a high degree of affinity, can adopt this type of accreditation due to the large number of benefits that are acquired in the management and linking between careers which allows a permanence of the culture of quality improvement.